PUBLIC PROCUREMENT DIGITALISATION AS A MECHANISM FOR TRANSPARENCY AND ANTI-CORRUPTION (CROSS BORDER MANAGEMENT STUDY): A SYSTEMATIC LITERATURE REVIEW - Sebastian; Maria Kalis; M. Irfani Hendri (Bridging Journal of Islamic Digital Economics and Management, 2026)
The digitalisation process in public procurement, which includes systems such as e- procurement, electronic government procurement, digital tendering, online auctions, and the use of analytics with risk modelling, has received considerable attention as an approach for improving transparency, enhancing operational efficiency, and reducing corruption. This systematic literature review aims to synthesize empirical evidence as well as conceptual findings on how the digitalisation of procurement affects four key areas: (1) transparency and accountability; (2) outcomes related to integrity, including anti-corruption measures and fraud prevention; (3) operational efficiency and value for money; and (4) competitive dynamics and supplier participation levels. The PRISMA 2020 protocol was followed for the review. Keywords such as "public procurement," "e-procurement," "transparency," and "efficiency" were used in Scopus searches, which were filtered by discipline relevance, English language, and open-access criteria. Out of 561 initial records, 23 studies met the inclusion criteria. The review found, through thematic synthesis, that digitalisation generally improves transparency by creating digital audit trails. Integrity is also strengthened through the implementation of control indicators and the use of risk-based analytics. Operational efficiency also improves. However, effects on supplier competition remain inconsistent. The success of the digitalisation of procurement systems depends heavily on the quality of institutional governance, the design of the systems, and the adequacy of national digital infrastructure.